Adipose Tissue–Derived Stem Cells From Obese Subjects Contribute to Inflammation and Reduced Insulin Response in Adipocytes Through Differential Regulation of the Th1/Th17 Balance and Monocyte Activation - Eljaafari, Assia; Robert, Maud; Chehimi, Marwa; Chanon, Stephanie; Durand, Christine; Vial, Guillaume; Bendridi, Nadia; Madec, Anne-Marie; Disse, Emmanuel; Laville, Martine; Rieusset, Jennifer; Lefai, Etienne; et al. (Diabetes (New York, N.Y.), 2015)
Obesity, through low-grade inflammation, can drive insulin resistance and type 2 diabetes. While infiltration of adipose tissue (AT) with mononuclear cells (MNCs) is well established in obesity, the functional consequences of these interactions are less understood. Herein, we cocultured human adipose-derived stem cells (ASCs) from obese individuals with MNCs and analyzed their reciprocal behavior. Presence of ASCs 1) enhanced interleukin (IL)-17A secretion by Th17 cells, 2) inhibited γ-interferon and tumor necrosis factor α secretion by Th1 cells, and 3) increased monocyte-mediated IL-1β secretion. IL-17A secretion also occurred in stromal vascular fractions issued from obese but not lean individuals. Th17 polarization mostly depended on physical contacts between ASCs and MNCs—with a contribution of intracellular adhesion molecule-1—and occurred through activation of the inflammasome and phosphatidylinositol 3-kinase pathways. ASCs favored STAT3 over STAT5 transcription factor binding on STAT binding sites within the IL-17A/F gene locus. Finally, conditioned media from activated ASC-MNC cocultures inhibited adipocyte differentiation mRNA markers and impaired insulin-mediated Akt phosphorylation and lipolysis inhibition. In conclusion, we report that obese- but not lean-derived ASCs induce Th17 promotion and monocyte activation. This proinflammatory environment, in turn, inhibits adipogenesis and adipocyte insulin response. The demonstration of an ASC-Th17-monocyte cell axis reveals a novel proinflammatory process taking place in AT during obesity and defines novel putative therapeutic targets.